2017
DOI: 10.1111/crj.12625
|View full text |Cite
|
Sign up to set email alerts
|

Oral health related quality of life depending on oral health and specific factors in patients after lung transplantation

Abstract: The oral health perception of LuTx patients does not reflect the apparent oral health deficiencies. Consequently, sensitization and motivation for an increased dental behavior is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 25 publications
(64 reference statements)
4
20
0
Order By: Relevance
“…A further similarity to the available literature is the missing association between oral health and OHRQoL for the patients within the current study, which has been repeatedly described and was hypothesized accordingly [8][9][10][11][12][13][14][15]. The nearly unaffected OHRQoL of the HTx and HF patients despite the high prevalence of periodontal treatment need in the current study is conspicuous, especially considering the effects of periodontitis on OHRQoL in generally healthy individuals [27].…”
Section: Comparison With Published Datasupporting
confidence: 69%
See 3 more Smart Citations
“…A further similarity to the available literature is the missing association between oral health and OHRQoL for the patients within the current study, which has been repeatedly described and was hypothesized accordingly [8][9][10][11][12][13][14][15]. The nearly unaffected OHRQoL of the HTx and HF patients despite the high prevalence of periodontal treatment need in the current study is conspicuous, especially considering the effects of periodontitis on OHRQoL in generally healthy individuals [27].…”
Section: Comparison With Published Datasupporting
confidence: 69%
“…Only one study had previously examined the OHRQoL of HTx patients, and it also showed a slight effect on the OHRQoL; however, the OHIP 49 questionnaire was used in the previous examination, making comparison of the values difficult [7]. Other previous studies performed on patients with solid organ transplantation showed slightly lower OHIP G14 scores compared to the current study; these studies focused on patients after kidney (2.54), lung (1.7) and liver (4.1) transplantation [8][9][10]. Without further results for patients with HF or organ transplantation, several other German patient groups with chronic systemic diseases might be considered to interpret the current study's findings.…”
Section: Comparison With Published Datamentioning
confidence: 62%
See 2 more Smart Citations
“…Moreover, although HTx group scored better than LVAD and HF, only the minority of participants rated that their oral hygiene behavior had changed since heart disease. This points out to an assumption concluded from studies regarding oral health-related quality of life of organ transplant recipients: an inappropriate estimation of the importance of oral health caused by the general disease burden [32][33][34]. In heart transplanted individuals, the perceived influence of oral health on quality of life was concluded to be reduced [35].…”
Section: Discussionmentioning
confidence: 95%